Effects of changes in judo rules on attacking efficiency index between the national championship of Bosnia and Herzegovina 2010 and 2014 year - Kajmovic, H.; Rado, I.; Crnogorac, B.; Mekic, A.; Kapo, S. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
In order to judo fight gets the highest possible intensity, the same conditions for both competitors to show their best performance and the ease of understanding and monitoring for viewers, International Judo Federation (IJF) has changed its rules in 2013. year. The aim of this research is to evaluate effects of changes in the rules of judo sport in attacking efficiency index techniques of judo between the National Championship of Bosnia and Herzegovina in 2010. year and 2014. year. siehe auch: https://www.researchgate.net/publication/273577373_EFFECTS_OF_CHANGES_IN_JUDO_RULES_ON_ATTACKING_EFFICIENCY_INDEX_BETWEEN_THE_NATIONAL_CHAMPIONSHIP_OF_BOSNIA_AND_HERZEGOVINA_2010_AND_2014_YEAR